Fighting breast cancer using membrane-active peptides - Almeida, Inês Filipa de Oliveira (2015)
Cancer is still one of the major death causes worldwide demanding an urgent search for new therapies that combine selectivity, efficacy and ability to avoid resistance by cancer cells. One of the biggest advances in anticancer therapy is the use of antimicrobial peptides’ (AMPs) as chemotherapy drugs since some of them showed both antimicrobial activity and selective anticancer activity. In this work, the anticancer activity of three different AMPs, pepR, HNP-1 and PvD1, was tested against cancer and non-tumorigenic breast cell lines (MDA-MB-231 and MCF 10A). The cytotoxic activity of each peptide was evaluated by MTT tetrazolium assay and the determination of the half maximal inhibitory concentration (IC50), and showed that pepR and PvD1 act as anticancer peptides (ACPs), able to select between cancer and non-tumorigenic cells, whereas HNP-1 is not a promising ACP once it is not selective, killing both cell lines at the same concentration. Then, zeta-potential was used to evaluate the peptide-cell interaction and its effect in cells’ surface charge. In this case, surface neutralization is not required before cell death, contrary to what happens when these peptides act like AMPs. Finally, according with previous results, PvD1 was chosen as the most promising peptide and, as such, used for imaging assays with atomic force microscopy (AFM). With this technique height profiles and surface roughness were evaluated for both cell lines in absence and presence of three different PvD1 concentrations. It was concluded that, with the increase of peptide concentration there are no significant changes in cell’s height profiles. On the other hand, when analysed separately, nucleus and cytoplasm present surface roughness changes associated to the increasing of PvD1 concentration. Although it is not yet possible to propose a mechanism of action, both pepR and PvD1 are efficient against MDA-MB-231 cells and selective to MCF 10A cells.